Exocrine pancreatic function in children with coeliac disease before and after a gluten free diet. Issue 7 (July 1991) - Carroccio, A; Iacono, G; Montalto, G; Cavataio, F; Di Marco, C; Balsamo, V; Notarbartolo, A
Abstract : This study was designed to determine the extent of pancreatic insufficiency in untreated coeliac disease and whether pancreatic secretion is impaired after a prolonged gluten free period. Three groups of patients were studied: group A comprised 44 patients, mean (SD) age 4.0 (3.1) years, with coeliac disease and total or subtotal atrophy of the intestinal mucosa; group B comprised 67 patients, mean age 4.4 (3.0) years, with coeliac disease but with normal morphology of the intestinal villi (after 12.9 months of a gluten free diet); group C comprised 49 control subjects, mean age 3.2 (3.0) years, with normal jejunal histology. In all subjects exocrine pancreatic function was determined by the secretin-caerulein test; bicarbonate concentration and lipase, phospholipase, and chymotrypsin activity were measured after an intravenous injection of secretin 1 clinical unit (CU) + caerulein 75 ng/kg body weight. Faecal chymotrypsin concentration was also assayed. No significant difference was found between values of the duodenal output of pancreatic enzymes and bicarbonate obtained in the three groups; however, 10 of 44 untreated coeliac patients showed tryptic or lipolytic activity, or both, below the normal limit for our laboratory. The mean value of the faecal chymotrypsin concentration was significantly lower in untreated than in treated coeliac patients (p less than 0.0001) or in control subjects (p less than 0.0001). It is concluded that untreated coeliac patients may have pancreatic deficiency independent of a decrease in enterohormone release. No primary or secondary pancreatic insufficiency was found in coeliac patients where the intestinal mucosa had returned to normal.